ANALISIS KINERJA KEUANGAN PADA DINAS PEMBERDAYAAN MASYARAKAT DESA PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN MUSI RAWAS UTARA - Suharto Patih; Miki Indika; Ismi Talia (Jurnal Kajian Akuntansi dan Auditing, 2022)
The purpose of this study was to determine the financial performance of the Department of Village Community Empowerment, Women's Empowerment and Child Protection, North Musi Rawas Regency. The data collection method that the author uses in this study is a method of collecting documentation data while the technical data analysis that will be used by the author is descriptive analysis, data analysis by explaining theories related to Financial Performance Analysis at the Village Community Empowerment Service, Women's Empowerment and Child Protection in North Musi Rawas Regency Fiscal Year 2016-. Based on the results of the research, the financial performance of the Village Community Empowerment, Women's Empowerment and Child Protection Office of North Musi Rawas Regency seen from the analysis of spending variance in 2016-2019 in general can be said to be good. This is indicated by the average realization target of 81.06%, and indicated by the absence of expenditure realization that exceeds the budget in each fiscal year and has made efficiency or budget savings